Numerical analysis of landslides caused by rainfall in a reduced physical slope model. Issue 8 (3rd July 2021) - Hamrouni, Fakher; Trabelsi, Houcem; Jamei, Mehrez; Olivella, Sebastia
Abstract: To assess slopes' movements as heavy rainfall consequences, the strategy to replace the field monitoring by the combination between the reduced physical model and numerical simulations can be envisaged. This strategy reduces the cost and makes the monitoring well efficiency by reducing its duration and considering variably saturated conditions. In this article, the macro gravity physical model is used as an alternative of the 1 g model. So, the hydraulic gradient method is proposed to follow the slope movements under different rainfall conditions. This method which is based on the increase of the mass force would avoid the use of centrifuge technique. It is studied numerically to demonstrate the optimum dimensions of the physical model and prioritizing the influence of the main parameters against the increase of mass forces. The before-failure behaviour was modelled by establishing an elastoplastic model based on the effective stress concept and non-associative Mohr–Coulomb yield function. The coupling between the strain and the suction was introduced using both the proposal effective stress–suction relation and the balance mass equations of solid and fluid. The validation of the proposal model was done using experimental results previously published. A good agreement between the numerical and experimental results was highlighted.